The Strategy of News Theme Consistency of Harian Bhirawa Mass Media in the Era of Popular Culture - Nikita, Nikita; Syadabila, Aishya; Prayogo, Moh. Dey (CONVERSE Journal Communication Science, 2025)
The emergence of popular culture has significantly transformed the landscape of mass media, including local outlets like Harian Bhirawa. Amid the rise of media outlets that follow popular culture trends to attract readers' attention, Harian Bhirawa remains consistent in delivering news focused on governmental issues, prioritizing depth and balanced reporting. This study aims to explore how Harian Bhirawa adjusts its news strategies to remain relevant and effective amidst these changes. A qualitative approach was employed through in-depth interviews and content analysis of digital platforms, specifically Instagram and the official website of Harian Bhirawa. The findings reveal that although Harian Bhirawa maintains its primary focus on governmental issues, it has begun optimizing digital platforms to reach younger audiences who are more active on social media. This study underscores the importance of flexibility and innovation for local media to sustain their presence in the competitive and dynamic era of popular culture.